A novel UTMD system facilitating nucleic acid delivery into MDA-MB-231 cells. Issue 2 (18th February 2020) - Zhang, Hui; Li, Yue; Rao, Fang; Liufu, Chun; Wang, Yi; Chen, Zhiyi
Abstract: Gene therapy is emerging as a promising method for the treatment of various diseases. The safe and efficient delivery of therapeutic nucleic acids is a gene therapy prerequisite. Ultrasound, particularly in combination with microbubbles composed of biocompatible materials such as lipid, PLGA and chitosan, is a novel non-viral tool for gene transportation. Under ultrasound irradiation, microbubbles explode and generate pores in the cell membrane. Hence, genes can enter cells more easily. In order to transfect nucleic acids into MDA-MB-231 cells in a low-cost and non-viral manner for further breast cancer gene therapy studies, we explored ultrasound targeted microbubble destruction (UTMD) technology and evaluated the efficiency and safety of the delivery of plasmid encoding enhanced green fluorescent protein (pEGFP) and a microRNA-34a (miR-34a) mimic by UTMD. Sonovitro ultrasonic apparatus was employed to generate ultrasonic field, which was developed by our group. Ultrasonic parameters, including acoustic intensity (AI), exposure time (ET) and duty cycle (DC), were optimized at 0.6 W/cm 2 AI, 20 s ET and 20% DC, the cell viability was not obviously impaired. Under these conditions, the UTMD-mediated transfection efficiency of pEGFP was greater than 40%. In addition to plasmid DNA, an miR-34a mimic was also successfully introduced into the cytoplasm by UTMD and found to inhibit proliferation, induce apoptosis of MDA-MB-231 cells and regulate downstream molecules. The present study indicates that further in vivo UTMD-mediated gene therapy studies are warranted.